FAKTOR - FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Ersita Damayanti, 12.05.52.0128; Nurhayati, Ida (Students Journal of Accounting and Banking, 2016)
This study aimed to analyze the effect of profitability, leverage, liquidity, firm size, ownership, and institutional ownership of the financial statements disclosure in the annual financial statements on Manufacturing Companies listed on the Indonesia Stock Exchange (IDX). This sample in this study are Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) of the years 2012-2014 as many as 228 companies. Sampling was purposive sampling method. Mechanical testing of the data is by using multiple linear regression analysis. The results of analysis show that the variable firm size significant positive effect on financial statements disclosure, while the profitability, leverage, liquidity, ownership, and institusional ownership no significant effect on financial statements disclosure on Manufacturing Companies listed on the Indonesia Stock Exchange of the years 2012-2014.Keywords: Profitability, Leverage, Liquidity, Firm Size, Ownership, Institutional Ownership, Financial Statements Disclosure